Analysis Of The Efficiency Of Using Solar Cells In The Electrical System Of Non-Conventional Ship - Tona, Tasdik; Nurwahidah, Nurwahidah; Dr. Nurwahidah, Dr. Nurwahidah; Asri, Haerani (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
This research aims to determine the efficiency of using solar cells in non-conventional ship electrical systems. The method that will be used in the research is the use of primary data and secondary data which will provide a comprehensive approach in this research. Based on the analysis above, a system with solar cells can produce Wh of energy per day, to meet daily energy needs with Wh of the Watts used every day. By using the battery capacity, the system has very large energy reserves, allowing the system to be used every day and will be very efficient in meeting load needs, with excess energy capacity. With a generator capacity with more than enough Wattage to meet the daily energy needs of the existing load, this means there is excess energy that can be stored in the generator.